Six Common Mistakes in Conservation Priority Setting - Game, Edward T (Blackwell Publishing Ltd, 2013)
ABSTRACT: A vast number of prioritization schemes have been developed to help conservation navigate tough decisions about the allocation of finite resources. However, the application of quantitative approaches to setting priorities in conservation frequently includes mistakes that can undermine their authors’ intention to be more rigorous and scientific in the way priorities are established and resources allocated. Drawing on well-established principles of decision science, we highlight 6 mistakes commonly associated with setting priorities for conservation: not acknowledging conservation plans are prioritizations; trying to solve an ill-defined problem; not prioritizing actions; arbitrariness; hidden value judgments; and not acknowledging risk of failure. We explain these mistakes and offer a path to help conservation planners avoid making the same mistakes in future prioritizations. Seis Errores Comunes en la Definición de Prioridades de Conservación RESUMEN: Se ha desarrollado un vasto número de esquemas de priorización para ayudar a que la conservación navegue entre decisiones difíciles en cuanto a la asignación de recursos finitos. Sin embargo, la aplicación de métodos cuantitativos para la definición de prioridades en la conservación frecuentemente incluye errores que pueden socavar la intención de sus autores de ser más rigurosos y científicos en la manera en que se establecen las prioridades y se asignan los recursos. Con base en los bien establecidos principios de la ciencia de la decisión, resaltamos seis errores comúnmente asociados con la definición de prioridades para la conservación: no reconocer que los planes de conservación son priorizaciones; tratar de resolver un problema mal definido; no priorizar acciones; arbitrariedad; juicios de valor ocultos y no reconocer el riesgo de fracasar. Explicamos estos errores y ofrecemos un camino para que planificadores de la conservación no cometan los mismos errores en priorizaciones futuras.